Efektifitas ekstrak daun kembang bulan (Tithonia diversifolia) terhadap gambaran histopatologi pankreas pada tikus yang diinduksi aloksan - Roeswandono Wirjatmadja; Rondius Solfaine; Dian Ayu Kartika Sari; Anisa Novia Wati (VITEK : Bidang Kedokteran Hewan, 2021)
This study was conducted to determine the histopathological picture of the pancreas by induction of alloxan and extracts of the moon flower (tithonia diversifolia) in wistar rats (rattus norvegicus). A total of 24 male Wistar rats with 4 treatments were control P0, alloxan P1 with 1% CMC Na, P2 alloxan with 100mg / kgBB extract, alloxan P3 with 200mg / kgBB extract. Mice after said diabetes mellitus with a number> 135 mg / dL were then given treatment with 1% CMC Na on P1 and lunar leaf extract at P2 and P3, necropsy was carried out on the 15th day and the pancreatic organs were taken to be made in the form of preparations with coloring. HE, lesions observed Degeneration, Inflammatory Cells and Necrosis using a microscope, the results were analyzed using Kruskal wallis followed by Mann withney. The data obtained by degeneration in the kruskal wallis test were very significantly different because there were significant differences (P = 0.01), inflammation cells in the Kruskal wallis test were very significantly different because there were significant differences (P = 0.00), and for necrosis in the Kruskal wallis test significantly different because there are significant differences (0.02).